Pengelolaan Museum Rudana Sebagai Daya Tarik Wisata Berbasis Kearifan Lokal Di Desa Peliatan Kecamatan Ubud Kabupaten Gianyar - Astrid Krisdayanthi; I Gusti Ketut Indra Pranatha Darma; Ni Made Desi Meliana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
Rudana Museum is an art museum located in Ubud, Gianyar, Bali and is used to exhibit and promote works of art in the form of paintings and sculptures by Balinese artists. Rudana Museum was founded by Nyoman Rudana, a painting collector who is also the owner of Rudana Fine Art Gallery and Genta Fine Art Gallery. Proper management is very important. This research will discuss how to manage Rudana Museum as a local wisdom-based tourist attraction in Peliatan Village, Ubud District, Gianyar Regency. The focus of this study focuses on three things, namely to determine the potential of Rudana Museum as a local wisdom-based tourist attraction in Peliatan Village, Ubud District, Gianyar Regency, how the management of Rudana Museum, and the implications for the community around Rudana Museum. This research is a type of research with qualitative methods and the determination of informants is done by purposive sampling. The results of the discussion show that Rudana Museum was founded on the basis of the idealism of its founder, Nyoman Rudana, where art is a universal thing, as a result, contributing to the process of harmonization between man and God (parahyangan), between man and man (pawongan) and man and the surrounding nature (palemahan) which is reflected in the Balinese philosophical concept of Tri Hita Karana, where art is very instrumental in helping to spread peace, prosperity and a sense of brotherhood among mankind worldwide. The management of Rudana Museum is based on the application of tourism management functions, namely (Planning, Organizing, Motivation, Actuating, Controlling). Rudana Museum also cooperates with other museums in Indonesia.